Putting participation into practice: An ethnographic study of sheltered workshops in the Netherlands and Portugal. (March 2023) - Sebrechts, Melissa; Tonkens, Evelien
Full participation is recognized as fundamental for the inclusion and wellbeing of people with intellectual disabilities. Only few studies have identified subjective meanings of participation from the perspective of people with intellectual disabilities themselves. Three cross-cutting themes that arise in the few studies that have are choice, social interaction and making a contribution . This ethnographic study of sheltered workshops in the Netherlands and Portugal takes this body of work a step further by investigating to what extent the ideal of participation is put into practice in such a way that it indeed contributes to these three elements. By including contrasting cases, it scrutinizes different ways of institutionalizing participation and the consequences this bears for the lived experiences of people with mild intellectual disabilities. The results show that there is a tension between choice on the one hand, and social interaction and making a contribution on the other.